Perlindungan Hukum Dan Tanggung Jawab Perusahaan Alfamart Yang Beroperasi 24 Jam Terhadap Karyawan Alfamart Yang Bekerja Pada Malam Hari: (Studi Kota Mataram) - Muhammad Zikril Amin; H. Lalu Husni (Fakultas Hukum Universitas Mataram, 2023)
This research is to discover and examine legal protection for Alfamart’s night-shifted employees who operated for 24 hours and what are the responsibility of this company in the occurrence of working incidents. This research can be categorized as empirical legal research. It is evident that legal protection for Alfamart’s employees who work 24 hours in the outlets has been in accordance with the existing regulations which cover economic, technical and social protections. The company takes responsibility in terms of work incidents that occurred.